Helping Malaysian youth move forward: unleashing the prime enablers - Hamzah, Azimi (Bahagian Komunikasi Korporat, Universiti Putra Malaysia, 2005)
Malaysian youth demonstrated a dramatic change in their lifestyles beginning in the late 80s when they became more tolerant towards internationalism through growing up with the communication liberalization. The scenarios of Malaysian youth in transition are not encouraging. As revealed from research findings there are shocking social trends developing among young people in key lifestyle areas and thinking patterns. The findings indicate that higher percentages of youth are engaging in risky behaviours as they leave adolescence and enter into early adulthood. As youth move from adolescence to adulthood, relevant enablers must promote a holistic approach to help youth take full advantage of the range of options at their disposal. The approaches must incorporate key universal competencies for youth to be successful as adults including health, social, cognitive/ creative, vocational, citizenship, and spiritual competencies. The prime enablers were identified through research and juxtaposing theories and models of youth that are relevant to the local scene. The author shares his experience in unleashing the potentials of three prime enablers: youth workers, youth organizations, and youth R&D. The focus is on developing youth workers as effective enablers who are knowledgeable and professional to fully maximize the unique relationships they share with young people; on transforming youth associations into efficient vehicles for change that must be youth driven, efficient and complementing formal education to fulfil the needs of youth: and on youth R&D that should serve as a knowledge data bank to enable concerned adults to use as inputs in providing life direction to young people in transition.